Solução numérica de EDOS de primeira ordem pelos métodos de Euler com auxilio computacional - SAGICA, Jonas Lobato (2023)
It is indispensable for professionals in the exact sciences to accurately equate and solve a variety of problems that may arise from an ordinary differential equation, thus, the search for methods that are as close as possible to the exact solution is extremely important. In view of this, we attempted to carry out a comparative analysis between two methods of numerical solution, the Euler method and the modified Euler method. To corroborate the study, ways and examples that could be expressed mathematically in the Scilab software were investigated, which was used as a computational aid for the demonstration of the results obtained and graphical analysis. From the results, it was possible to perform this comparison between the methods and it is concluded that the modified Euler method is more accurate than the Euler method for presenting mathematical results that originate from the resolution of a first order ordinary differential equation.